Pola Resistensi Bakteri Terhadap Antibiotik pada Penderita Infeksi Luka Operasi (ILO) Di RSUP Dr. Soeradji Tirtonegoro Klaten Periode Agustus 2013-Agustus 2015 - Wiguna, Dian Septi, Prof. Dr. M Kuswandi,SU., M.Phil., Apt, Ratna Yuliani, M.Biotech.St (2016)
Surgical wound infection is an infection that occurs in the area of operations and is a major complication that often occurs after surgery. Antibiotics used in the treatment of surgical wound infections should be based on the pattern of bacterial resistance to antibiotics. Otherwise, it would have an impact on the increase of bacterial resistance to antibiotics. One of the important things that must be considered in treatment of the infection is the development of bacteria resistance to antibiotics that may complicate the treatment. The purpose of this study was to determine the infectional bacterial and patterns of bacterial resistance to antibiotics and the appropriateness of the definitive antibiotic use based on the results of bacteria sensitivity test in patients with surgical wound infection at Hospital Dr. Soeradji Tirtonegoro Klaten during 14 August 2013-31 August 2015. This study was a non-experimental study with retrospective data collection from 48 patients with surgical wound infection from 14 August 2013 to 31 August 2015 at the Hospital Dr. Soeradji Tirtonegoro Klaten. Data retrieved in this research were data on the use of antibiotics, bacterial culture and antibiotic sensitivity test results. Data were analyzed descriptively. Based on this research, the most dominant bacteria isolated from wound swabs and pus swab specimens from 48 patients with surgical wound infection at the Hospital Dr. Soeradji Tirtonegoro Klaten in the period of 14 August 2013-31 August 2015 were Enterobacter sp. and Staphylococcus aureus each percentage 16,22%. The bacterias have high levels of resistance to ceftriaxone (83%), erythromycin (100% and 33%), cefixime (83% and 92%), tetracycline (83% and 75%) and ciprofloxcacin (67% and 58%). The results of the appropriateness analysis in the definitive antibiotic use in patients with surgical wound infection shows that 41,82% of definitive antibiotics were given in accordance with the results of culture and bacterial sensitivity test results and the spectrum antibiotics activity.